The history of the devil : as well ancient as modern - Defoe, Daniel, 1661?-1731 (The Floating Press, 2012)
This fascinating volume from the author of such influential novels as Robinson Crusoe and Moll Flanders offers an analytical take on the figure of Satan. Although Defoe offers a comprehensive history of the symbolic and literary significance of the devil, he also believes that the devil plays an active and direct role in determining the course of world events, which he outlines in great detail.